(untitled) (International Journal of Engineering and Computer Science, 2013)
Today, Cricket is a very popular game worldwide. Cricket is a bat and ball game played between two teams of 11 players on a roughly circular field. It involves a bowler, a batsman and fielders. The bowler bowls to the batsman and tries to get him out while the batsman tries to score and hitting a ball. In cricket two factors are too much important and these factors are hitting speed & bowling speed. In this paper we look at various techniques that have been used to propose in recent years to measures the speed of bat and ball in cricket. This paper gives introduction about cricket in section 1. Section 2 tells the various methods suggested to measure speed in cricket. Finally section 3 concludes the paper.